Ways of Trading on Suvarnabhumi Route - Chatrathaisang, Piravat; Piriyasanguanpong, Dr. Sura (Journal of Dhamma for Life, 2023)
Suvarnabhumi is the name of the continental mainland of Southeast Asia, a name that has been used since ancient times. The long southern peninsula of the mainland is situated between the Andaman Ocean to the west and the South China Sea to the east, halfway between India and China. Suvarnabhumi is rich in mineral resources, including copper and tin, and it boasts advanced mineral fusion technology. By fusing copper and tin in the right proportions, these minerals transform into a shiny, bright gold-like metal known as bronze. Bronze quickly became a highly demanded export product in global markets, reaching as far as the Greco-Roman Empire. Throughout history, the commercial development of Suvarnabhumi has played a crucial role in connecting the civilizations of the Eastern and Western worlds, solidifying its status as the "Golden Land." In the present day, in the Indo-Pacific region, a new Silk Road of the 21st century has emerged, known as the "Belt and Road Initiative (BRI)." This project, in its economic dimension, involves integrating transportation links with infrastructure and production bases across various countries. This initiative fosters greater connections, allowing for flexible capital flow, trade, commercial investment, and technology exchange, ultimately driving economic growth in trading partner countries. Thailand is taking the lead with the Land Bridge project, which will link to new primary shipping routes, thus transforming global transportation in alignment with the Suvarnabhumi trade route. To enhance the quality and standards of economic development within the Suvarnabhumi territory, it is essential to focus on emphasizing the strengths of differentiation and preserving the uniqueness of each region, all while incorporating the wisdom and diversity of traditional cultures within the territory. This approach will enable Suvarnabhumi to strengthen its ties with China, India, and the Western world simultaneously.